An Action Research on Improving Parents’ Digital Advertising Literacy Skills - Ahmet Ayhan; Hediye Aydoğan (Türkiye İletişim Araştırmaları Dergisi)
Parental mediation plays a leading role in the process of shaping children’s relations with and raising awareness about digital advertisements. This study aims to qualitatively evaluate the effectiveness of the digital-based education model created to develop digital advertising literacy skills that parents need in this process. For this purpose, the action research model, which is one of the qualitative research methods, was adopted in the study and a 12-hour digital-based training was conducted with the participation of seven parents with children between the ages of 7 and 13 living in Antalya. Semi-structured interview was used to collect research data. The qualitative data obtained through semi-structured interview and observation were qualitatively content-analyzed in the MAXQDA 2020 analysis program. The results obtained from the qualitative data showed that the education model contributed to the development of parents’ skills in terms of conceptual, attitudinal and performance dimensions of digital advertising literacy. It was determined that this improvement also reflected positively on parental mediation strategies. Based on the results of the research, suggestions were made to researchers, practitioners and policy makers working in this field.